Promosi Jabatan dan Masa Kerja dalam Meningkatkan Kepuasan Kerja Karyawan di Perusahaan Daerah Air Minun Kabupaten Ogan Komering Ulu (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
At the Regional Water Company of Ogan Komering Ulu Regency, this study examines the role that years of service and position promotion have in raising employee job satisfaction. Questionnaires were sent as part of the research's data gathering strategy. In all, sixty-six people made their homes there. The data analysis approach that was utilized was Multiple Linear Regression. A t-value of 2.676 from the partial analysis reveals that job promotions at the Regional Water Utility in OKU Regency significantly influenced employee satisfaction. The duration of employment influenced job satisfaction among employees at the OKU District Regional Water Company, as indicated by a t-value of 7.073. The F value of 86.776 and R² of 0.734 were obtained from the analysis of the relationship between job satisfaction with tenure and promotion levels at the OKU Regency Regional Drinking Water Company. This showed that job advancement and length of service contributed 73.4% to job satisfaction, with other factors not included in the study, including education, work experience, perspective, and work attitude, accounting for the remaining 26.6%.